The Assessment of the Biocompatibility of Dental Alloys and Alloys for Dental Amalgam. Part Second - Z. Broukal; V. Fialová; J. Novotný (Czech Dental Chamber, 2014)
Background: The second part of the literature review on the biocompatibility of dental alloys is focused to their possible sensibilizing effects, mutagenicity and carcinogenicity and the methods of their testing. The condition of an allergic reaction to the metal alloy is releasing its components (metal ions) by corrosion processes. From the general mechanisms of allergic reactions is well known that metal ions alone can not be allergens. However, they may play a role of haptens, where they bind to certain body molecules (proteins, nucleic acids, carbohydrates) or modified. Tests allergenic properties of metals can only be performed in vivo, in animals or humans, and commonly used patch tests are both far from the situation in the mouth, and secondly, their explanatory power is ambiguous. It is often difficult to determine whether an inflammatory reaction to the metal ions is mediated by allergic mechanism or is a toxic reaction, or combination of both mechanisms. Mutagenicity is usually tested in bacterial cultures and carcinogenicity in long-term exposure studies in laboratory animals. Direct evidence of mutagenicity and carcinogenicity of the real dental alloys are not available, however potential of some metals from dental alloys in this regard this admits. Alloys for dental amalgams have among the other dental alloys exceptional position in the evaluation of their biocompatibility,w as the usual tests address the final product, ie dental amalgam, which is produced by mixing the alloy powder with mercury under specified conditions. The vast majority of studies dealing with the corrosive properties of amalgam, its biocompatibility and methods of testing is therefore focused on the impact of mercury release. Technical standards EN ISO 10993 together with EN ISO 7405, regarding the evaluation of biocompatibility of medical devices and therefore dental alloys give a set of tests, the implementation of which should be considered before a new product is introduced into use. The results of these preclinical tests in vitro and in vivo have only limited value and can not replace long-term clinical experience.